2008
DOI: 10.5194/bg-5-1311-2008
|View full text |Cite
|
Sign up to set email alerts
|

Influences of observation errors in eddy flux data on inverse model parameter estimation

Abstract: Abstract. Eddy covariance data are increasingly used to estimate parameters of ecosystem models. For proper maximum likelihood parameter estimates the error structure in the observed data has to be fully characterized. In this study we propose a method to characterize the random error of the eddy covariance flux data, and analyse error distribution, standard deviation, cross-and autocorrelation of CO 2 and H 2 O flux errors at four different European eddy covariance flux sites. Moreover, we examine how the tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 28 publications
4
83
0
Order By: Relevance
“…First, there can be annual biases in the eddy covariance measurements, due to imperfect data filtering and to gap-filling, which are large when compared to annual averages of the data, but, a priori, not when compared to monthly averages (Luyssaert et al, 2009;Lasslop et al, 2010). The weight of these biases for data averages is far larger than that of random measurement errors on individual data since the autocorrelation in time for these errors is negligible (Lasslop et al, 2008). Eddy covariance sites often also show large sinks which are due to the regrowing nature of local ecosystems for many of these sites (Jung et al, 2011), while the actual sink should be smaller in the larger scale model grid cells which merge such regrowing ecosystems with near-equilibrium of disturbed ecosystems.…”
Section: Protocol and Justificationmentioning
confidence: 99%
See 2 more Smart Citations
“…First, there can be annual biases in the eddy covariance measurements, due to imperfect data filtering and to gap-filling, which are large when compared to annual averages of the data, but, a priori, not when compared to monthly averages (Luyssaert et al, 2009;Lasslop et al, 2010). The weight of these biases for data averages is far larger than that of random measurement errors on individual data since the autocorrelation in time for these errors is negligible (Lasslop et al, 2008). Eddy covariance sites often also show large sinks which are due to the regrowing nature of local ecosystems for many of these sites (Jung et al, 2011), while the actual sink should be smaller in the larger scale model grid cells which merge such regrowing ecosystems with near-equilibrium of disturbed ecosystems.…”
Section: Protocol and Justificationmentioning
confidence: 99%
“…Figure 2 shows the averages over all the time and space locations when and where CE-L4 data are available during each 30-day period within the CHIMERE domain, of the prior and inverted NEE at 0.5 ‱ resolution and of the CE-L4 data. The spatial averaging over the different CE-L4 locations in Europe and over 30-day periods is assumed to strongly decrease the random measurement errors in the CE-L4 data (Lasslop et al, 2008) as well as the differences of representativity between these data and the estimates from the model which should be high when considering individual CE-L4 measurements (at a scale smaller than 1 km 2 ) and the corresponding 0.5 ‱ ×0.5 ‱ model grid cells, but which are assumed to be random, uncorrelated between the different measurement sites and not fully correlated over time at a given site. This assumption is supported by the good fit obtained by BR2011 between inverted estimates of NEE and spatially averaged CE-L4 data despite large misfits at individual sites.…”
Section: Protocol and Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using measurements across different types of forest ecosystems, Richardson et al (2008) found that the random measurement errors range approximately from 0.2 to 0.8 gC m −2 d −1 , being somewhat proportional to the absolute flux magnitude, which means that the variance due to the measurement errors accounts for 1 to 25 % of the total observation variance. Additionally, Lasslop et al (2008) showed that no significant measurement error correlation remains at the daily time scale. From these elements, we conclude that the seasonal structure of the model error in ORCHIDEE is very similar to that of the observation error described above (the orange curve in Fig.…”
Section: Temporal Structure Of the Observation Errormentioning
confidence: 99%
“…From this half-hourly data we compute daily means, in order to take advantage of the rapidly-declining autocorrelation of gap-filled halfhourly fluxes (see Fig. 5a in Lasslop et al, 2008).…”
Section: Flux Datamentioning
confidence: 99%